IMPROVING SOCIO-LEGAL MECHANISMS FOR PROTECTING CHILDREN FROM HARASSMENT AND VIOLENCE AND ENHANCING PREVENTION STRATEGIES - Otajonov Abrorjon Abrorjon (PT. Antis International Publisher, 2026)
Objective: This study offers a comprehensive analysis of the multifaceted issue of harassment and violence against children within Uzbekistan's contemporary legal framework, examining the characteristics of minor victimization and the role of the child victim in crime dynamics. Method: The research employs formal-legal, comparative-legal, and systemic approaches, utilizing empirical data from court records and forensic psychiatric evaluations to analyze child victimization. Results: The study identifies significant gaps in the current legal system, particularly the absence of specific aggravating circumstances for violence perpetrated by extended family members or child welfare professionals. Novelty: The research contributes to the field by proposing innovative, practical strategies for improving child protection, including the implementation of socio-emotional learning programs in schools, the creation of national screening and risk assessment standards, and the establishment of a specialized child protection hotline/task force. These measures aim to shift the focus from repressive to preventive approaches, highlighting the importance of psychological correction for offenders and digital monitoring for at-risk children.